Extremophilic Cellulases: A Comprehensive Review - Mohanta, Subham; Bahuguna, Megha; Baley, John David; Sharma, Shivika; Sharma, Vikas (Universitas Gadjah Mada, 2023)
Microbial cellulases are an important industrial enzyme having diverse applications in biotechnology, environmental challenges, industrial products and processes. Extremophiles like thermophillic bacteria are a good source of industrially important cellulases as these can withstand industrially rigorous procedures like paper deinking, fabric material softening, bio stoning, paper and pulp, biopolishing cloth material, animal feed and juice. Identification of novel cellulases or improving them through biotechnological interventions has remained a challenge for researchers. Genetic manipulation of thermophilic bacteria for increased cellulase production or synthetic biology approaches for cellulase gene/gene cluster extraction from thermophilic bacteria and expression in appropriate hosts for improved cellulase synthesis. The classic and high-throughput technologies like genomics, metagenomics and bioinformatics could be exploited to isolate cellulase genes from a variety of thermophilic bacteria and further processing. Keeping in view the ultimate requirement of extremophilic cellulases in industries, present study is a compilation of various aspects related to extremophilic cellulases their sources, production, biotechnological interventions and challenges.